Evaluation of Normal Heart Rate in Early Pregnancy Corresponding to Gestational Age between Six to Eight Weeks - Jha, Akhilesh Kumar; Rimal, Bikranta; Khatun, Tarannum (Med Phoenix, 2017)
Background: Ultrasonography is the reliable and safe way for the evaluation of pregnancy. Heart rate can be detected more confidently from the Ultrasonography. Heart rate is an important parameter for the evaluation of early pregnancy. The purpose of this study was to evaluate the normal heart rate in embryos/fetuses between 6 and 8 weeks of gestation. Method: In our region people are poor and most of them do not know the benefit of regular follow up examination during pregnancy. So most of pregnant women come to our centre at late stage of pregnancy. The number of pregnancy cases is good in our centre but the number of early pregnancy cases coming to regular follow up examination is low. Thus the study was conducted in 51 normal singleton pregnancies undergoing routine ultrasound examination during the first trimester of pregnancy. The duration of study was 6 weeks. Result: Out of 51 singleton pregnancies, 20 cases (39.2%) heart rate were between 131-150 beat per minute and 25 cases (49.0 %) heart rate were between 151-170 beat per minute. However 4 cases (7.8%) were between 110-120 beat per minute and 2 cases (3.9%) were more than 171 beat per minute. There were zero cases above the 180 beat per minute. Conclusion: The result of this study will help to evaluate abnormal and normal fetal heart rate so that early clinical decision whether to continue the pregnancy or terminate it can be taken, as Ultrasonography is only the method used in screening fetal well being in most of the region of our country. Med Phoenix Vol.2(1) July 2017, 34-37